Polemik Riwayat Abū Thālib Wafat dalam keadaan Kafir: Studi Naqd al-Matn - Muhammad Tahir Alibe (Diroyah : Jurnal Studi Ilmu Hadis, 2021)
This article aims to examine the history of Abū Thā lib, who died an infidel. Even though throughout his life, Abū Thā lib was  immortalized to serve his nephew Muhammad bin Abdullah who would later become a prophet at the end of time. From the time of the Prophet to adulthood, before and after being  appointed as a Prophet, Abū Thā lib was never separated from the Prophet. The death of his uncle made the Prophet very sad, which is called al-huzn in history. However, history does not record him as a true believer but does record him as a person who died under suspicious circumstances. Meanwhile, Abū Sofyan, whose life was  filled with hatred for Islam, was registered as a person who died in a state of faith. Abū sofyān was the Prophet's friend, while Abū Thā lib was not the Prophet's friend. Therefore, research on Abū Thā lib is a fundamental thing to do. This study uses library research type with the Naqd matn approach. The validity of sanad is not always in line with the authenticity of the existing hadith. If the reason for the hadith is invalid, then the hadith is  rejected. Bukhari, Muslim, al-Nasā i and Imam Ahmad bin Hanbal reported that Abū Thā lib died as an infidel so that the majority of Muslims believed in Abū Thalib's distrust. The Naqd al-Matn approach shows that this hadith can not be valid because it contradicts historical facts and common sense.